Projection of SDGs in codes of ethics: Case study about lost in translation - Adam P. Balcerzak; Radka MacGregor Pelikánová (Administrative Sciences, 2020)
The United Nations' (UN) drive for sustainability culminates in a recent milestone document, Agenda 2030, which sets forth 17 Sustainable Development Goals (SDGs). Arguably, these SDGs inspire governments more than they do individual businesses and their embracement and measurement at the business level faces a myriad of shortcomings. A case study of internal declaratory documents about sustainability and other ethical commitments, such as codes of ethics, represents a feasible platform to collect fresh and inside primary data about the projection of SDGs in these codes of ethics, and ultimately in the strategy and daily operations of involved businesses. The representativeness of the sample of 30 businesses is ensured by the size of these businesses, their inter-related nature, and significance in the EU. A holistic approach, along with meta-analysis, comparison, and a combination of automatic keyword-based content analysis and of a manual simplified Delphi-method, allows for the addressing of both underlying burning questions-(i) how SDGs are projected in these codes of ethics and (ii) why not in a perfect manner. The main five findings point out the deep conceptual misunderstandings and shortcomings by businesses, which do not properly work with their codes of ethics, and which could take at least partially the SDG's guidance. These rather pioneering propositions are not conclusive, due to the inherent and inevitable limitations of the performed case study, and need to be verified over time (longitudinally), while expanding the pool of studied codes of ethics.
Keywords: 350; code of ethics; Sustainable Development Goals (SDGs); content analysis